(untitled) (KYAMC Journal, 2023)
Hepatitis A super infection can cause severe or even fatal illness in patients with chronic liver disease. Here, we describe a ten-year-old boy who was admitted for acute hepatitis A virus infection but later on he was diagnosed with Wilson disease. Wilson disease was diagnosed on the basis of low ceruloplasmin, high urinary copper excretion, and the presence of K-F ring. Hepatitis A was diagnosed by the presence of antibody in the blood. This case report suggests that acute hepatitis A virus infection may play a role in acute decompensation in diagnosed or undiagnosed chronic liver disease. KYAMC Journal Vol. 13, No. 04, January 2023: 261-263